Flame-retardant fire-resistant electromagnetic shielding carbon composite material based on waste biomass material and preparation method of flame-retardant fire-resistant electromagnetic shielding carbon composite material
By using expanded flame retardants composed of ammonium polyphosphate, melamine, urea, etc. in electromagnetic shielding textiles, a high-carbon content carbon fabric-based composite material is formed, which solves the problem of reduced electromagnetic shielding effect of existing electromagnetic shielding textiles in fire environments, and achieves good electromagnetic shielding and flame retardant performance in flame environments, and simplifies the preparation process.
Patent Information
- Application Number
- CN202411886951.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Existing electromagnetic shielded textiles are prone to lose their conductive network in fire environments, resulting in a reduction in electromagnetic shielding effect. In addition, the preparation of traditional carbonized materials requires high temperature and inert gas conditions, which consumes a long time and high energy consumption.
An expanded flame retardant (IFR) composed of ammonium polyphosphate, melamine and urea is mixed with waste biomass material, loaded on the fabric by ultrasonic dispersion and spraying, and then carbonized in an air atmosphere to form a carbon fabric-based composite material with a high carbon content.
It achieves the maintenance of good electromagnetic shielding performance in a flame environment, and has good flame retardant performance. The preparation process is simple, fast and efficient, without inert gas, reducing energy consumption and production costs.
Smart Images

Figure CN119638424A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flame-retardant electromagnetic shielding materials, and more specifically relates to a flame-retardant and fire-resistant electromagnetic shielding carbon composite material based on waste biomass materials and a preparation method thereof. Background Art
[0002] As electronic devices continue to miniaturize and become more complex, electromagnetic interference issues have become increasingly prominent in various fields, including consumer electronics, medical technology, and the automotive industry. Electromagnetic interference shielding textiles, characterized by their soft and lightweight properties, have been widely used in flexible wearable devices and sensors. However, the complexity of the application environment coupled with the inherent flammability of these textiles has raised concerns about fire hazards. Zhang Sheng's team (Sustainable Materials and Technologies, 2024, 40, e00949) alternately deposited MXene and polyphosphoramide on PA6 fibers, and its electromagnetic shielding effect reached 24dB, while its limiting oxygen index increased from 19% to 25.5%. However, these materials will be exposed to flame environments. The conductive network will be destroyed and lose the electromagnetic shielding effect. Therefore, the development of electromagnetic shielding textiles with flame retardant properties that can maintain their flame-retardant electromagnetic interference shielding effect in the event of a fire can effectively mitigate fire-related damage and protect the data integrity of internal electronic components and devices.
[0003] Carbonized materials are lightweight, high temperature resistant, have excellent electrical conductivity, thermal conductivity and chemical stability, and are widely used as conductive materials, refractory materials and photothermal conversion materials. The Kong Jie team of Northwestern Polytechnical University (Carbon, 2024, 227, 119268) carbonized phosphorylated wood at 600°C for 210 min in a nitrogen atmosphere to prepare carbonized wood, which had an electromagnetic shielding effect of 52 dB and good flame retardant properties. The Zhang Yingying team of Tsinghua University (Advanced Functional Materials, 2017, 27(2), 1604795) carbonized cotton fabric for 200 min in a mixed atmosphere of argon and hydrogen to prepare carbonized textiles with good electrical conductivity for use in high-sensitivity wearable sensors. However, this traditional method for preparing carbonized materials requires high temperature and inert gas conditions, which is time-consuming and energy-intensive. Therefore, it is of great significance to explore the rapid preparation of carbonized materials in an air atmosphere.
[0004] Biomass materials are a widely existing carbon source in nature, mainly composed of cellulose, hemicellulose, and lignin. During the pyrolysis process, organic matter decomposes to form stable carbon. However, in industrial production and life, a large amount of biomass materials are discarded during processing, such as bamboo powder, rice husks, coffee grounds, etc., which is inconsistent with the current energy conservation and emission reduction policies. Therefore, it is of great research significance to develop a fast, environmentally friendly, and efficient method for preparing efficient, flame-retardant, and durable electromagnetic shielding carbon-based composite materials from waste biomass materials. Summary of the invention
[0005] The main purpose of the present invention is to address the above-mentioned problems and provide a flame retardant and fire-resistant electromagnetic shielding carbon composite material based on waste biomass materials and a preparation method thereof. By loading an intumescent flame retardant (IFR), a slightly inert atmosphere environment is provided. By introducing waste biomass materials, the overall carbon content is increased, and the integrated preparation of high-temperature and rapid flame retardant electromagnetic shielding materials is achieved. The raw materials are easily available, the material is low-carbon and energy-saving, and the process is fast and efficient.
[0006] The core idea of the present invention is to use an IFR composed of ammonium polyphosphate, melamine, and urea, wherein ammonium polyphosphate as an acid source will produce acidic substances such as phosphoric acid to promote the carbonization of the matrix, and melamine as a carbon source will form a dense carbon layer through its own carbonization during the pyrolysis process, and urea as an acid source will produce ammonia during the pyrolysis process to form a slightly inert atmosphere, and at the same time help to form an expanded carbon layer. The three play a synergistic role in a specific proportion to form a uniform and stable carbon layer while maintaining the integrity of the internal structure. Waste biomass materials often have a high carbon content and are renewable. The synergistic addition of them with IFR effectively increases the carbon source content during the carbonization process, helps to form a thicker and stronger carbon layer, and at the same time, the integrated molding quickly and efficiently obtains a high-carbon content carbon fabric composite material, the overall fire resistance of the material is high, and the electromagnetic shielding durability is good.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] One of the technical solutions of the present invention: a method for preparing a flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials, comprising the following steps:
[0009] S1, mixing an intumescent flame retardant with a waste biomass material, adding water and performing ultrasonic dispersion, and loading the resulting mixture on a fabric by spraying, and then drying to obtain a modified fabric-based composite material;
[0010] S2. The modified fabric-based composite material prepared in S1 is sandwiched between two quartz plates and carbonized together to obtain a flame-retardant and fire-resistant electromagnetic shielding carbon composite material.
[0011] Further preferably, in step S1, the intumescent flame retardant is a compound of ammonium polyphosphate, melamine and urea.
[0012] Further preferably, in step S1, in the intumescent flame retardant, ammonium polyphosphate accounts for 50-90% of the total mass of the flame retardant, melamine accounts for 5-30% of the total mass of the flame retardant, and urea accounts for 5-20% of the total mass of the flame retardant.
[0013] Further preferably, in step S1, the average molecular weight of the ammonium polyphosphate is >1000.
[0014] Further preferably, in step S1, the surface density of the intumescent flame retardant loaded on the fabric is 5-25 mg / cm 2 Further preferably, in step S1, the surface density of the intumescent flame retardant loaded on the fabric is 10-25 mg / cm 2 .
[0015] Further preferably, in step S1, the surface density of the waste biomass material loaded on the fabric is 2-30 mg / cm 2 .
[0016] Further preferably, in step S1, the surface density of the waste biomass material loaded on the fabric is 10-30 mg / cm 2 .
[0017] Further preferably, in step S1, the surface density ratio of the intumescent flame retardant to the waste biomass material is 0.5-3:1.
[0018] Further preferably, in step S1, the waste biomass material is one or more of sawdust, rice husk, bamboo powder, coconut shell, bagasse and coffee grounds.
[0019] Further preferably, in step S1, the drying is performed at a temperature of 50-70°C.
[0020] Further preferably, in step S2, the carbonization atmosphere is an air atmosphere.
[0021] Further preferably, in step S2, the carbonization temperature is 500-1200° C., and the carbonization time is 5-30 min.
[0022] The second technical solution of the present invention: a flame retardant and fire resistant electromagnetic shielding composite material obtained by the above preparation method.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] (1) Compared with the preparation of traditional carbon fabric-based composite materials, the carbonization atmosphere of the carbon fabric-based composite materials prepared by the present invention is simply air atmosphere.
[0025] (2) Compared with the preparation of traditional carbon fabric-based composite materials, the carbon fabric-based composite materials prepared by the present invention are prepared quickly through integration, with low carbonization temperature and short time.
[0026] (3) Compared with traditional electromagnetic shielding materials, the carbon fabric-based composite material prepared by the present invention has good flame retardant properties and can maintain good electromagnetic shielding properties in a flame environment.
[0027] (4) The present invention uses an intumescent flame retardant and waste biomass materials as raw materials to quickly and efficiently prepare a carbon fabric-based composite material. Compared with the preparation of traditional carbonized materials, the steps are simple, no inert gas requirements are required, the yield is high, the raw materials are easily available, the cost is low, and it can be mass-produced and used. At the same time, the carbon fabric-based composite material prepared by integrated carbonization has good flame retardant and electromagnetic shielding properties, and can be widely used in communications, electromagnetic protection, aerospace and other fields, and has excellent application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The combustion condition of the flame retardant and fire resistant electromagnetic shielding carbon composite material of the present invention exposed to an alcohol lamp;
[0029] Figure 2 The conductivity and electromagnetic shielding performance of the IFR-Cot-W sample; (a) initial conductivity of the IFR-Cot-W sample; (b) initial electromagnetic shielding performance of the IFR-Cot-W sample; (c) conductivity of the IFR-Cot-W sample after exposure to flame; (d) electromagnetic shielding performance of the IFR-Cot-W sample after exposure to flame;
[0030] Figure 3 The conductivity and electromagnetic shielding performance of the IFR-Cot-C sample; (a) initial conductivity of the IFR-Cot-C sample; (b) initial electromagnetic shielding performance of the IFR-Cot-C sample; (c) conductivity of the IFR-Cot-C sample after exposure to flame; (d) electromagnetic shielding performance of the IFR-Cot-C sample after exposure to flame;
[0031] Figure 4 The conductive properties and electromagnetic shielding properties of the IFR-Cot-B sample; (a) initial conductive properties of the IFR-Cot-B sample; (b) initial electromagnetic shielding properties of the IFR-Cot-B sample; (c) conductive properties of the IFR-Cot-B after exposure to flame; (d) electromagnetic shielding properties of the IFR-Cot-B sample after exposure to flame. DETAILED DESCRIPTION
[0032] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0033] Example 1
[0034] S1. 70wt% ammonium polyphosphate, 20wt% melamine, and 10wt% urea are selected to form IFR and mixed with waste sawdust, diluted with deionized water and ultrasonically dispersed evenly. The resulting mixture is then loaded on the fabric by spraying, and the surface density of the IFR loaded on the fabric is controlled to be 10mg / cm 2 The surface densities of waste biomass materials are 10, 15, and 20 mg / cm 2 , and then placed in a 60℃ oven for drying.
[0035] S2. Place the modified fabric-based composite material prepared above between two quartz plates, put it into a muffle furnace at 700°C for carbonization for 20 minutes in an air atmosphere, and prepare a flame-retardant and fire-resistant electromagnetic shielding carbon composite material IFR-Cot-W. Table 1 shows the preparation parameters of IFR-Cot-W.
[0036] In order to characterize its electromagnetic shielding performance, flame retardant performance and fire stability, a four-point probe instrument was used to test the conductivity; a vector network analyzer was used to test the electromagnetic shielding performance; an alcohol lamp was used to burn its flame retardant performance, and the conductivity and electromagnetic shielding performance after exposure to flame were tested.
[0037] Table 1 IFR-Cot-W preparation parameters
[0038]
[0039] Example 2
[0040] S1. 75wt% ammonium polyphosphate, 16wt% melamine, and 9wt% urea were selected to form IFR and mixed with waste coffee grounds, diluted with deionized water and ultrasonically dispersed evenly. The resulting mixture was then loaded on the fabric by spraying, and the surface density of the IFR loaded on the fabric was controlled to be 10mg / cm 2 The surface densities of waste biomass materials are 10, 15, and 20 mg / cm 2 , and then placed in a 65℃ oven for drying.
[0041] S2. The modified fabric-based composite material prepared above is placed between two quartz plates, and carbonized in a muffle furnace at 1000°C for 10 minutes in an air atmosphere to obtain a flame retardant and fire resistant electromagnetic shielding carbon composite material IFR-Cot-C. Table 2 shows the preparation parameters of IFR-Cot-C.
[0042] In order to characterize its electromagnetic shielding performance, flame retardant performance and fire stability, a four-point probe instrument was used to test the conductivity; a vector network analyzer was used to test the electromagnetic shielding performance; an alcohol lamp was used to burn its flame retardant performance, and the conductivity and electromagnetic shielding performance after exposure to flame were tested.
[0043] Table 2 IFR-Cot-C preparation parameters
[0044]
[0045] Example 3
[0046] S1. 75wt% ammonium polyphosphate, 16wt% melamine, and 9wt% urea are selected to form IFR and mixed with waste bamboo powder, diluted with deionized water and ultrasonically dispersed evenly. The resulting mixture is then loaded on the fabric by spraying, and the surface density of the IFR loaded on the fabric is controlled to be 10mg / cm 2 The surface densities of waste biomass materials are 10, 15, and 20 mg / cm 2 , and then placed in a 70℃ oven for drying.
[0047] S2. The modified fabric-based composite material prepared above is placed between two quartz plates, and carbonized in a muffle furnace at 900°C for 15 minutes in an air atmosphere to obtain a flame retardant and fire resistant electromagnetic shielding carbon composite material IFR-Cot-B. Table 3 shows the preparation parameters of IFR-Cot-B.
[0048] In order to characterize its electromagnetic shielding performance, flame retardant performance and fire stability, a four-point probe instrument was used to test the conductivity; a vector network analyzer was used to test the electromagnetic shielding performance; an alcohol lamp was used to burn its flame retardant performance, and the conductivity and electromagnetic shielding performance after exposure to flame were tested.
[0049] Table 3 IFR-Cot-B preparation parameters
[0050]
[0051] Example 4
[0052] S1. 75wt% ammonium polyphosphate, 16wt% melamine, and 9wt% urea are selected to form IFR and mixed with waste bamboo powder, diluted with deionized water and ultrasonically dispersed evenly. The resulting mixture is then loaded on the fabric by spraying, and the surface density of the IFR loaded on the fabric is controlled to be 5mg / cm 2 、10mg / cm 2 、15mg / cm 2 , 20mg / cm 2 , the surface density of waste biomass materials is 10 mg / cm2 , and then placed in a 70℃ oven for drying.
[0053] S2. The modified fabric-based composite material prepared above is placed between two quartz plates, and carbonized in a muffle furnace at 900°C for 15 minutes in an air atmosphere to obtain a flame retardant and fire resistant electromagnetic shielding carbon composite material IFR-n-Cot-B. Table 4 shows the preparation parameters of IFR-n-Cot-B.
[0054] In order to characterize its electromagnetic shielding performance, flame retardant performance and fire stability, a four-point probe instrument was used to test the conductivity; a vector network analyzer was used to test the electromagnetic shielding performance; an alcohol lamp was used to burn its flame retardant performance, and the conductivity and electromagnetic shielding performance after exposure to flame were tested.
[0055] Table 4 IFR-n-Cot-B preparation parameters
[0056]
[0057] Comparative Example 1
[0058] Pure cotton fabric was placed between two quartz plates in a muffle furnace at 900°C for 15 minutes to prepare a carbon fabric-based composite material Pure-Cot.
[0059] Comparative Example 2
[0060] The IFR composition and parameter conditions of Example 3 were adopted, no waste biomass material was added, and other conditions were kept exactly the same to prepare a carbon fabric-based composite material IFR-C.
[0061] Comparative Example 3
[0062] The carbon fabric-based composite material IFR-APP was prepared by selecting an IFR composition consisting only of ammonium polyphosphate and adopting the parameter conditions of Example 3 without adding waste biomass materials and controlling other conditions to be exactly the same.
[0063] Comparative Example 4
[0064] The IFR composition was selected to be 80 wt% ammonium polyphosphate and 20 wt% melamine, and the parameter conditions of Example 3 were adopted. No waste biomass material was added, and other conditions were controlled to be exactly the same to prepare the carbon fabric-based composite material IFR-APP-Melamine.
[0065] Comparative Example 5
[0066] The IFR composition was selected to be 75 wt % ammonium sulfate, 16 wt % cellulose, and 9 wt % sodium bicarbonate, and the parameter conditions of Example 3 were adopted, while other conditions were controlled to be exactly the same, to prepare the carbon fabric-based composite material IFR2.
[0067] Comparative Example 6
[0068] Using the IFR composition and parameter conditions of Example 3, the surface density of the waste bamboo powder is 50 mg / cm 2 The surface density ratio of IFR to waste biomass material is 1:5, and other conditions are kept exactly the same to prepare the carbon fabric-based composite material IFR-Cot-B-5.
[0069] Table 5 Test results of electrical conductivity and electromagnetic shielding performance
[0070]
[0071]
[0072] Table 6 Test results of electrical conductivity and electromagnetic shielding performance after exposure to flame
[0073]
[0074]
[0075] like Figure 1 As shown, according to the combustion conditions of the samples exposed to an alcohol lamp, it can be known that the carbon fabric-based composite material prepared in the present invention has good flame retardant properties, does not produce shrinkage and flame spread phenomena under the alcohol lamp, maintains good morphological integrity, and has good flame retardant properties.
[0076] like Figure 2 , 3 As shown in Figure 4, according to the conductivity of the sample before and after exposure to flame, the initial resistance value of the material is low and has good conductivity. At the same time, with the increase of the waste biomass loading, its conductivity shows an upward trend. This is because the waste biomass is mainly composed of cellulose and lignin, and graphite-like biochar is formed during the carbonization process. At the same time, the granular biochar forms a more complete conductive structure network, which improves the electronic conductive channel and improves the conductivity. And higher conductivity means that there are more free electrons on the surface of the material. When electromagnetic waves are incident on the surface of the conductive material, the free electrons respond quickly and reflect electromagnetic waves, so the electromagnetic shielding performance is improved. After being exposed to flames, its resistance changes little, and the overall electromagnetic shielding performance decreases slightly, but it can still meet the commercial 20dB requirement, indicating that the material has good fire resistance stability.
[0077] As shown in Table 5 and Table 6, by comparative analysis, it is found that ammonium polyphosphate, melamine and urea are selected and used in combination according to the claims, and the best electromagnetic interference shielding effect can be achieved in a suitable proportion with waste biomass materials. This is because the acid source ammonium polyphosphate in the intumescent flame retardant releases phosphoric acid and other substances during pyrolysis to catalyze carbonization, while melamine is a good carbon source. Urea, as a gas source, will produce ammonia and the like during pyrolysis, diluting the concentration of oxygen and producing a slightly inert environment. The synergy of the three and the combination with an appropriate amount of waste biomass materials can maximize carbonization and have the best electromagnetic interference shielding effect. Excessive load of waste biomass materials will reduce the basic mechanical properties of the material and cause shedding, resulting in reduced electromagnetic shielding effect.
[0078] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0079] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials, characterized in that: The steps include: S1, mixing an intumescent flame retardant with a waste biomass material, adding water and performing ultrasonic dispersion, and loading the resulting mixture on a fabric by spraying, and then drying to obtain a modified fabric-based composite material; S2. The modified fabric-based composite material prepared in S1 is sandwiched between two quartz plates and carbonized together to obtain a flame-retardant and fire-resistant electromagnetic shielding carbon composite material.
2. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials as claimed in claim 1, characterized in that: In step S1, the intumescent flame retardant is a compound of ammonium polyphosphate, melamine and urea.
3. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials as claimed in claim 2, characterized in that: In step S1, in the intumescent flame retardant, ammonium polyphosphate accounts for 50-90% of the total mass of the flame retardant, melamine accounts for 5-30% of the total mass of the flame retardant, and urea accounts for 5-20% of the total mass of the flame retardant.
4. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials as claimed in claim 1, characterized in that: In step S1, the surface density of the intumescent flame retardant loaded on the fabric is 5-25 mg / cm 2 .
5. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials as claimed in claim 1, characterized in that: In step S1, the surface density of the waste biomass material loaded on the fabric is 2-30 mg / cm 2 .
6. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials according to any one of claims 1 to 5, characterized in that: In step S1, the surface density ratio of the intumescent flame retardant to the waste biomass material is 0.5-3:
1.
7. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials according to any one of claims 1 to 5, characterized in that: In step S1, the waste biomass material is one or more of wood chips, rice husks, bamboo powder, coconut shells, bagasse and coffee grounds.
8. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials as claimed in claim 1, characterized in that: In step S2, the carbonization atmosphere is an air atmosphere.
9. The method for preparing the flame retardant and fire resistant electromagnetic shielding carbon composite material based on waste biomass materials as claimed in claim 1 or 8, characterized in that: In step S2, the carbonization temperature is 500-1200°C, and the carbonization time is 5-30 minutes.
10. The flame retardant and fire resistant electromagnetic shielding carbon composite material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Flame-retardant modified carbon fiber prepreg and composite material product
CN104553177A
Biomass graphene-modified fire retardant and master batch and preparation method
CN106467616A
Method for microwave pyrolysis of carbon fiber composite material
CN111100322A
Porous composite material capable of generating electric arc in microwave field, preparation method therefor, and use thereof
CN112823441A
Flame retardants for cellulose-containing materials
DE102021119885A1